Smart textile coatings and laminates - Smith, W. C. (Woodhead publishing in textiles, 2010)
Coatings and laminates allow for the introduction of smart functionalities for textile products. They are suitable for a wide range of textile applications and can contribute to improving product performance. This pioneering book is a valuable reference and stimulus for developing and improving coated and laminated textile products.